THE IMPACT OF IMPLEMENTING TECHNOLOGY IN THE DEVELOPMENT OF OPEN INNOVATION AND ENVIRONMENTALLY FRIENDLY INNOVATION ON DIGITALIZATION IN MSMES - Ainun Sakinah L Tobing; Ritha F Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
In the current digital era, the application of technology has brought significant changes and opportunities for micro, small and medium businesses. This has also led to the development of open innovation, where companies collaborate with external partners to create and share new ideas and solutions. The application of digital technology has facilitated innovation in overcoming environmental challenges. This technological progress has also paved the way for digitalization in MSMEs. By adopting digital technology, MSMEs can streamline their operations, automate processes, and increase productivity, thereby enabling MSMEs to increase their competitiveness and performance in the market, as well as accelerating the digital transformation of MSMEs that allows them to adapt and thrive in the digital economy. This research uses the literature review method, literature review aims to solve problems. We can draw conclusions from the results of the literature review. By developing technological solutions to social and environmental problems, MSME owners have the potential to become a positive force in creating sustainable social and economic change.